Nietzsche asceta - Sousa, Mauro Araujo de (2005)
Ascetism became known for the efforts made by metaphysician to reach their spiritual purpose. Nietzsche published a critique on ascetical ideals in the III Dissertation of the Genealogy of Morals because ascesis had taken transcendental life as a reference for all values beyond this life which is immanent. An ascetic metaphysical morality emphasized the dualism this life another life , which Nietzsche contested by stating it had philosophically originated with Plato as morality against nature . Thus, by returning to the cradle of Western culture, Nietzsche propounds a revision of ascesis based on transcendence, immutability, and truth from the standpoint of life, this life a constant flow, concerned exclusively with change, with outward aspects. In a nutshell, such ascesis refers to becoming a follower of Dionysus, to lead a dionysian life: a whirl of forces that continuously come together and apart, creating centres of will to power, giving rise to everything alive or, in other words, everything that appears and disappears into what is commonly called reality . Therefore, anyone willing to go further ahead of what is ordinary in the contemporary world could only demand of oneself the utmost self-overcoming, the utmost self-control in order to attain a quintessential spiritualization of instincts instead of the sterilization that transcendent values have long prescribed to the body as a rule for life. This hypothetical being is embodied in ascetic Nietzsche , here represented as a dionysian ascetic set against the ascetical ideal